The roles of technology in enhancing service excellence in higher education - Ariffin, Hasfizani; Mohd Mokhtar, Sany Sanuri; Abdullah, Nur Farhana (978-967-2276-11-1, 2019)
For a long time, the importance of technology has become an essential topic discussed for competitive advantage and previous studies have pointed out that many business operations have shifted from traditional to computer since the 1980s (Jackson & Humble 1994). During that time, the information technology was considered as a new way in delivering products and services in the business environment to be ahead from their competitors (Jackson & Humble, 1994). The technology support was told has improved customer’s satisfaction, by aiding the organization's communication processes (Johnson, Fidler & Rogerson, 1998; Jackson & Humble 1994). For ages, technology was named as the major factor in improving the organization’s performance. More than two decades ago, a study by Johnson et al. (1998) has named the technological support in a business environment during that time such as fax, electronic mail, mobile phones, messaging services and video conference facilities and personal computer. The study justified that the organizational change was probably lagging behind the technological innovation, which is still equivalent to the current situation since fast-growing technology is expensive and some high skills need to be applied. This statement was supported by a recent study which related to today’s huge market with a competitive environment that caused by technology which required different approaches to tackle new customer’s demand and behaviour (Kotler, Kartajaya & Setiawan, 2016). Indeed, nowadays the technology has a direct impact on the organization performance, such as the accessibility of information to their customers, suppliers and distributors (Tay & Low, 2017). Regardless of any business in any industry, immediate response to the internet community that rely on their community’s recommendation has reduced the organization power in marketing their products and services (Kotler et al.,2016).